2023
DOI: 10.1038/s43856-022-00233-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of BNT162b2 and CoronaVac in children and adolescents against SARS-CoV-2 infection during Omicron BA.2 wave in Hong Kong

Abstract: Background The SARS-CoV-2 Omicron BA.2 subvariant replaced BA.1 globally in early 2022, and caused an unprecedented tsunami of cases in Hong Kong, resulting in the collapse of elimination strategy. Vaccine effectiveness (VE) of BNT162b2 and CoronaVac against BA.2 is unclear. Methods We utilize an ecological design incorporating population-level vaccine coverage statistics and territory-wide case-level SARS-CoV-2 infection surveillance data, and inv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 42 publications
0
30
1
Order By: Relevance
“…However, S IgG avidity and cellular immunogenicity against Omicron were maintained, which can possibly explain the persistently high real-life vaccine effectiveness even when it is known that there is waning of quantitative serum antibody concentrations against VOCs. 5,12 Indeed, several human studies have shown that T cell immunity can persist for years after prior exposure and mitigate disease severity when neutralising antibodies are reduced, and the pre-existing antigen-specific T cells are protective against influenza viral infections, severity of symptoms and viral shedding. [32][33][34][35][36] In addition, vaccine-induced T cell responses against the highly conserved structural SARS-CoV-2 membrane protein confers partial protection from lung pathology in a murine model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, S IgG avidity and cellular immunogenicity against Omicron were maintained, which can possibly explain the persistently high real-life vaccine effectiveness even when it is known that there is waning of quantitative serum antibody concentrations against VOCs. 5,12 Indeed, several human studies have shown that T cell immunity can persist for years after prior exposure and mitigate disease severity when neutralising antibodies are reduced, and the pre-existing antigen-specific T cells are protective against influenza viral infections, severity of symptoms and viral shedding. [32][33][34][35][36] In addition, vaccine-induced T cell responses against the highly conserved structural SARS-CoV-2 membrane protein confers partial protection from lung pathology in a murine model.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the strict social distancing policies that the HK Government mandated during the COVID-19 period kept infection numbers low so that it was not possible to investigate vaccine efficacy in this cohort during this study period, from April 2021 to August 2022 (see Methods). 1,5,12 On the other hand, this provided the opportunity to determine the intradermal vaccine immunogenicity without the confounding effects of existing immunity acquired from past infections. 1,5,12 Moreover, we were able to estimate actual vaccine efficacies using neutralising antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that a significant amount of secondary transmission may occur prior to the symptomatic disease onset, thus facilitating the epidemic. In the fifth wave of HK, the effective Rt remained persistently high even in a context with relevant fully vaccination coverage [23] (see also the “ false colours” contour plot in Figure 1), probably due to the scarce effectiveness of BNT162b2 and CoronaVac against Omicron VOC, especially in children and adolescents [24] .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that a significant amount of secondary transmission may 6 occur prior to the symptomatic disease onset, thus facilitating the epidemic. In the fifth wave of HK, the effective Rt remained persistently high even in a context with relevant full vaccination coverage [22] (see also the "false colors" contour plot in Figure 1), probably due to the scarce effectiveness of BNT162b2 and CoronaVac against Omicron VOC, especially in children and adolescents [23].…”
Section: Discussionmentioning
confidence: 99%